North-East Nigeria Recovery and Peace Building Assessment : State Reports - World Bank Group (Washington, DC: World Bank, 2016)
Since 2009, insecurity in the North-East of Nigeria has led to the loss of over 20,000 lives and the displacement of over two million people. Throughout the region livelihoods have been disrupted, and homes, public buildings and infrastructure destroyed. In a part of Nigeria where 80 percent of people rely on agriculture for their livelihoods, much has been lost. People have been forced from their land and livestock has been killed. In many areas, land mines and other remnants of war bring challenges for safe and voluntary return. While Borno, Adamawa and Yobe States bore the brunt of the direct impacts of the conflict, the three neighboring states of Gombe, Taraba and Bauchi have taken in scores of people who have been displaced, taxing their communities, economic resource, social services and infrastructure. Schools have been damaged, health clinics destroyed and many people have been left vulnerable by this crisis. The Government of Nigeria has made great strides in retaking and stabilizing large portions of the North-East, but the work to restore the lives of those affected is just beginning. This assessment, led by the Government of Nigeria and supported by local, national and international partners, has helped quantify the physical, social and economic impacts of the crisis in the North-East, and will inform the process of stabilization, peace building and recovery in the region. The RPBA is a necessary tool that will help us gather the resources and develop the capacities to address these challenges. The results will help reduce suffering in affected communities, restore a sense of normalcy and regain the trust of people in the region.